Kebijakan Dividen Sebagai Pemoderasi Dan Pengaruhnya Terhadap Likuiditas, Leverage Dan Profitabilitas Pada Nilai Perusahaan (Kasus Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2017-2019) - Parida, Parida; Surasni, Ni Ketut; Suryawati, Baiq Nurul; Hidayati, Siti Aisyah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
This study aims to determine the effect of liquidity, leverage and profitability to the firm value with dividend policy as moderating variables in Manufacturing company listed on the Indonesia Stock Exchange (IDX) in 2017-2019.This type of research is associative quantitative research. The data collection method used is Sample Survey method. The population in this study are all manufacturing companies listed on Indonesia Stock Exchange (IDX) of 182 companies. Sampling method with purposive sampling. And based on the criteria of the number of samples as many as 66 out of 182 companies. data analysis using multiple regression analysis with Moderated Regression Analysis (MRA).The results showed that: Liquidity significant positive effect on firm value. Leverage significant positive effect on firm value. Profitability significant positive effect on firm value. Dividend policy is able to strengthen the effect of liquidity on the firm value. Dividend policy weakens the effect of leverage on the firm value. Dividend policy is not able to strengthen the effect of profitability on the firm value